PERANCANGAN MEDIA PROMOSI PROGRAM STUDI DESAIN KOMUNIKASI VISUAL UNIVERSITAS NEGERI PADANG BERBASIS ANIMASI - AULIA ULFA, Yahya, Hendra Afriwan (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
The purpose of designing a media campaign this animation is, (1) to design a media campaign of Visual Communication Design Program better right through the animation medium, interesting and informative, (2) produce a concept and visualization that can be used as a media campaign that is more attractive DKV Studies Program, (3) is expected to increase the interest of new students to choose the media through Short DKV From Animation (SFA), (4) may provide an explanation and information to the public against DKV Studies with clear and on target. In the design method of data sources derived from observation, interviews, and documentation related to study Graphic Design Program, and in the discussion of the work of data analysis using the SWOT method can infer how important design issues that needed to be promoted and to know the strengths and deficiencies and minimize opportunities for threats to media promotion. design results in the form of a media campaign based animation that is packaged in a CD or DVD can be used for a media campaign in the Graphic Design department of each yearKata Kunci : Promosi, DKV, Animasi.